Facilities management development in Europe. (21st November 2008) - Maliene, Vida; Alexander, Keith; Lepkova, Natalija
Facilities Management (FM) uses different approaches and has distinctive priorities in very particular country. There are widely divergent interpretations of the FM concept as it is used in various countries. FM is generally understood in the similar way, but it may use different strategies. There is as yet no consistent definition of the scope of FM activities. The study reported here concerns one general question: why are FM definitions different? We investigate how the historical backgrounds of different countries influence the development of FM, and reveal how the individual law system, psychology and business environment affects FM in various countries.